PEMILIHAN HARDWARE PEMBUATAN DATA LOGGER ONLINE MONITORING KUALITAS AIR BERBASIS MAINBOARD PC DAN OPEN SOURCE SOFTWARE - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2014)
Real-time water quality monitoring requires data logger for automatic data retrieval by sensors. The hardware data logger for realtime monitoring can be developed by utilizing scars computer mainboard that are still functioning and widely avaliable in the market at low prices. Through online monitoring applications that developed by using free open source software, water quality data can be measured in accordance with the specified time interval and stored in the database system. This paper discusses the hardware selection and recomendation studies that include the motherboard and CPU, storage, transmission and communication medium required for the manufacturing of computer's mainboard based data logger. The results of this study are to be used as an alternative data logger selection for realtime water quality monitoring with low investment costs. So, the water companies can monitor raw water quality from their water treatment plant as well as the industrial can monitor wastewater quality from wastewater treatment plant. Keyword : online monitoring, real time monitoring, early warning system (EWS), open source software, data logger, onlimo OSS.